Development and evaluation of a brief treatment for cannabis-related problems - Fetterling, Theodore J., author; Prince, Mark, advisor; Conner, Bradley, committee member; Riggs, Nathaniel, committee member (Colorado State University. Libraries, 2021)
Cannabis use and related problems have shown a consistent increase among young adults in recent years despite abstinence being the predominant goal for most treatments. Research indicates that many individuals with problematic cannabis use do not seek treatment due to a desire to continue using. Whereas abstinence assumes any use to be problematic, harm reduction offers a comparably effective alternative that is conducive to reductions in use or problems as the primary goal of treatment. However, research exploring harm reduction as a standalone treatment for cannabis is underdeveloped. Another challenge facing cannabis treatment is the wide variability in training procedures and evaluation of therapist adherence to intervention protocol reported in the relatively few cannabis-specific treatment studies conducted to date. The current study addressed these disparate treatment concerns through the development of a harm reduction treatment for cannabis, establishment of a standardized approach for therapist training and evaluation, and testing the feasibility of this intervention against a healthy stress management (HSM) control condition. Methods. Prior treatment studies were used to inform the selection of intervention components for the cannabis-specific treatment (CST). The HSM condition was adapted from a web-based version where it also served as a control condition. Study therapists were trained on the CST and HSM protocols using manual review, didactic training, and role plays. Adherence to treatment protocols was assessed using fidelity checklists developed for use with each unique study condition. The analytical sample (n = 16) consisted of community members interested in treatment and undergraduate students participating for research credit. A 2x2 ANCOVA tested for intervention effects on cannabis-related problems while controlling for sex. Descriptive statistics and clinical significance were used to assess therapist training and fidelity, as well as selected participant outcomes. Results. Therapist training showed high rates of attrition, with fewer than half of therapists completing all stages. Among therapists who completed all stages of training, fidelity checks indicated high protocol adherence rates across study conditions. Although no treatment effect for reduction of cannabis-related problems was detected, several participants reported clinically significant increases or decreases on measures of distress, dependence, use frequency, and goal attainment. Discussion. Findings suggest that use of a standardized, multimethod training paradigm facilitates high rates of therapist adherence to manualized treatment protocol. The potential for the present study to be used as a template for development of a therapist training model in future work is discussed. Though preliminary analyses did not support the CST as efficacious for cannabis-related problem reduction, there was a trend toward higher goal attainment for participants who received the CST. Goal type endorsement also aligned with prior findings that alternatives to abstinence-based programming for cannabis are needed.
Keywords: intervention development; cannabis; therapist training